Paget-Schroetter Syndrome: a case report of diagnosis, treatment, and outcome in a healthy 18-year-old athletic swimmer - El-Attrache, A.; Kephart, E. (The Physician and Sportsmedicine, 2020)
Paget-Schroetter Syndrome is a rare condition in the spectrum of deep vein thromboses involving spontaneous upper extremity venous thrombosis in the axillary-subclavian vein. The syndrome usually occurs in young, healthy individuals and is a progressive, anatomic manifestation of venous thoracic outlet syndrome. Thrombosis is secondary to repetitive overuse of the arm, leading to compression, microtrauma, and local inflammation of the particularly vulnerable subclavian vein in the thoracic outlet at the junction of the first rib and clavicle. The condition is often misdiagnosed because of its rarity and can lead to significant disability and morbidity if treatment is delayed. In this case report, Paget-Schroetter Syndrome, causing significant pain and dysfunction, is presented in an 18 year-old female freestyle-swimmer that was successfully treated with anticoagulation, thrombolysis, thoracic outlet decompression and first rib resection, scalenectomy, venolysis, and venoplasty. Early suspicion of this condition can lead to prompt diagnosis, and subsequent aggressive interventional treatment with catheter-directed thrombolysis and thoracic outlet decompression, in addition to anticoagulation, demonstrated success in achieving complete resolution of symptoms in this case.